The T-Virus experiment and human cloning: A narrative analysis of Grace Ashcroft’s character and the Marie and Emily Project in Resident Evil 9 Requiem - Wahyudi Wahyudi (Priviet Social Sciences Journal, 2026)
The development of digital technology has transformed video games into entertainment media and platforms for conveying complex narratives related to social, scientific, and ethical issues in modern society. One of the most prominent franchises that consistently presents themes of biological experimentation and biotechnology is the Resident Evil series. This study aims to analyze the representation of T-Virus experimentation and human cloning in Resident Evil 9 Requiem through the narrative roles of Grace Ashcroft, Leon S. Kennedy, Sherry Birkin, Marie, Emily, and antagonists such as Dr. Victor Gideon and Zeno. This study employed a qualitative descriptive method using narrative, thematic, and character analyses. The data sources included cutscenes, character dialogues, official trailers, and gameplay walkthrough videos from YouTube streamers, such as MiawAug and Windah Basudara. The findings reveal that the T-Virus experiment is a symbol of dehumanization and the collapse of humanity caused by unethical scientific ambition. Furthermore, the cloning project involving Marie and Emily reflects issues of identity crisis, psychological conflict, and ethical dilemmas surrounding artificial humans and genetic manipulation in the narrative. The study also found that Elpis symbolizes dystopian science and the moral collapse resulting from uncontrolled biotechnology development. Therefore, Resident Evil 9 Requiem not only functions as a survival horror game but also serves as a medium for reflecting contemporary bioethical issues and the dangers of scientific misuse in modern society.